Women in modern terrorism: from liberation wars to global Jihad and the Islamic State - Davis, Jessica (Rowman & Littlefield, 2017)
Introduction: women in modern terrorism -- Organizational decision making -- Gender and the radicalization process(es) -- Lebanese Hizballah and Palestinian terrorist groups -- Women in ethno-nationalist conflict -- Women in global Jihad: from Al Qaeda to Chechnya -- Evolving global jihad: Boko Haram and Al Shabaab -- Women's role in the conflict in Iraq and Syria -- Conclusion: trends in female terrorism